Dissecting the Relationship Between Study Time, Gender, and Age: A Holistic Approach to Understanding Academic Performance in Contemporary Education - Selina, Hendriani; Anggraini, Tyas; Amanda Konoralma, Rahel; Wilson Setiawan, Andreas; Atsala Vindramekka, Rajwa; Arga Satya, Hazel; Sofia Wibowo, Syifa (International Journal of Health Literacy and Science, 2024)
Academic performance is a complex and multifaceted outcome shaped by cognitive, behavioral, and biological factors influencing students' academic performance. This study aimed to investigate the relationships between the student’s study time, gender, age, and academic performance in a sample of students. The study used correlation and comparative statistical methods to explore how these variables might influence student grades. The correlation between study time and grades was found to be weakly positive (p = 0.037, R = 0.105), indicating that while more study time is associated with slightly better grades, the strength of this relationship is modest. The comparative analysis between male and female students revealed a significant difference in average grades, with male students achieving higher grades (p = 0.041). The average grade for male students was 10.91, while female students averaged 9.97. Additionally, the correlation between age and academic performance was negative (p = 0.001, R = -0.173), suggesting that as students age, their academic performance tends to decline, albeit weakly. These findings underscore the complexity of factors influencing academic success, suggesting that study time, gender, and age play a role, but their impacts may vary in strength. The results highlight the need for further research to explore the cognitive, social, and biological factors that interact with these variables and contribute to students' academic performance. The modest correlations suggest that other variables, such as study strategies, motivation, and neurobiological factors, maybe more substantial in determining academic success.